The Relationship Between Ethnocentrism and Students' Intercultural Tolerance in the Context of Multicultural Counseling - Nuraisah Rizki Syahputri (Jurnal Counseling Care, 2025)
As guidance and counseling teachers, of course we will always meet clients from different cultures. The purpose of this study is to find out if there is a relationship betweena ethnocentrism and student tolerance in multicultural counselling. This study uses a quantitative method using a research instrument developed by ourselves, namely a questionnaire. Data analysis technique used determination coefficient analysis, namely parametric statistics with Pearson correlation test to find out how strong the relationship between ethnociticism variables and student tolerance attitudes, using SPSS Statistics 26 software. The sample in this study is 33 students from diverse ethnic backgrounds and different campus backgrounds. Samples were taken randomly. The results of this study show that there are 4 students with ethnocentrism in the high category, and 29 students have ethnocentrism in the medium category. And there were 31 students who had a tolerance in the high category, and 2 students had a tolerance in the medium category. This shows that although students have moderate ethnocentrism traits of 88%, they are also able to control it, which is evidenced by the high tolerance trait of 94%. In table 5, it is known that the Pearson correlation value (r) is 0.692 with a significant level of >0.05 so it is concluded that there is a positive relationship or correlation between ethnocentrism and student tolerance, based on table 6 the r value of 0.692 is in a strong interpretation. So that the positive level is in a strong relationship. The results of this research are expected to be a reference for future researchers if they want to research the same thing.